Constellations of Support: A Community Development Model - Melba Spooner; Tracy Smith (To Improve the Academy)
This article describes the rationale, development process, and initial artifacts and outcomes of a faculty support (a.k.a. mentoring) model developed for a specific academic context: a College of Education at a Southeastern comprehensive public university. The purposes of this article are to (1) describe the research and theoretical models that guided the development of the program; (2) provide a research-based rationale for a context-based community development model of faculty support; (3) propose a set of principles for a context-based developmental community model of faculty support; (4) describe the process for developing a community development mentoring model for faculty at all career levels; and (5) offer artifacts, tools, and activities that faculty developers and institutions may use or adapt for their own context-based communities of support.